Short Synthesis Time and Characterization of Dialdehyde Carboxymethyl Cellulose (DCMC) from High Bagasse Carboxymethyl Cellulose (CMCB) Concentration - Kamonwan Tachai; Aree Deenu; Suthaphat Kamthai (Journal of Natural Fibers)
Bagasse is a type of bast fiber obtained from agricultural waste. It is a suitable material for producing cellulose derivatives, specifically as a DCMC crosslinking agent. The optimal synthesized conditions of dialdehyde carboxymethyl cellulose (DCMCB) from the elemental chloride-free (ECF) bleached bagasse pulp were evaluated, including the concentration of bagasse carboxymethyl cellulose (CMCB) at 3% and 6% (w/v), the sodium periodate (NaIO4) concentration at 5%, 10%, and 15% (w/v) and the reaction time from 1 to 4 hours. The optimal conditions were characterized based on the DCMCB properties, including production yield, aldehyde content, and degree of oxidation. The optimal conditions for synthesizing DCMCB are a pH of 3.0, a reaction temperature of 35°C, a NaIO4-to-CMCB mass ratio of 1:6, and a reaction time of 2.5 hours. It obtained 97.37% yield and 97.70% aldehyde content. This optimal condition led to a 27.2% significant increase in DCMCB aldehyde content and a 37.5% reduction in reaction time. Various analytical techniques were employed to verify the success of CMCB oxidation and to fully characterize the crystallinity, thermal stability, and structure of DCMCB. CMCB encountered oxidation, resulting in alterations in functional groups and influencing the crystallinity, thermal stability, and structure of DCMCB.